Building - Wilkinson, Philip, 1955-; King, Dave; Dann, Geoff (New York : Knopf : Distributed by Random House, 1995)
Describes the art and technique of how things are built, from mud huts to city skyscrapers.
"A Dorling Kindersley book"--T.p. verso.
Includes index.
Wilson's Children.
Wilson's Junior High School.
Elem. School Library Collection.
6.5
Keywords: Structural engineering -- Juvenile literature; House construction -- Juvenile literature; Building materials -- Juvenile literature; Structural engineering; House construction; Building materials; Structural engineering; House construction; Building materials; Structural engineering; House construction; Building materials